Islamic Tradition and Religious Culture in Halal Tourism: Empirical Evidence from Indonesia - M. Sugeng Sholehuddin; Munjin Munjin; Hendri Hermawan Adinugraha (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2021)
Indonesia as a country with the largest Muslim population in the world, Indonesia also has a lot of cultural and traditional potential that can be elaborated in halal tourism attractions. This study aims to describe Islamic tradition and religious culture in halal tourism in terms of empirical evidence from Indonesia. This research is a qualitative study using the literature (literature) from previous studies. The library research procedure in this research begins in detail with the selection of topics, then explores information, determines the focus of research, collects data sources, reads data sources, makes research notes, processes research notes, and ends with drawing conclusions. Data collection techniques in this study used editing, organizing, and finding. Data analysis in this study used deductive and interpretative methods. The results show that Islamic tradition and religious culture in the halal tourism industry has a very important role in the halal tourism industry. These two elements are the main attraction in the attraction of halal tourism destinations in In- donesia. Tourists can learn and feel about Islamic tradition and religious culture in halal tourism packages that have religious and kindness values. The integration of Islamic tradition and religious culture in halal tourism is allowed in Islam as long as it does not conflict with Islamic law.